2013
DOI: 10.1007/s10616-013-9597-8
|View full text |Cite
|
Sign up to set email alerts
|

Tempol prevents genotoxicity induced by vorinostat: role of oxidative DNA damage

Abstract: Vorinostat is a member of histone deacetylase inhibitors, which represents a new class of anticancer agents for the treatment of solid and hematological malignancies. Studies have shown that these drugs induce DNA damage in blood lymphocytes, which is proposed to be due to the generation of oxidative lesions. The increase in DNA damage is sometimes associated with risk of developing secondary cancer. Thus, finding a treatment that limits DNA damage caused by anticancer drugs would be beneficial. Tempol is a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Therefore, the use of SAHA may increase risk of cancer. However, a very recent study showed that the antioxidant Tempol prevents genotoxicity induced by SAHA and may, potentially, alleviate the long-term risks of the drug [147]. Hence, further detailed studies are required to develop safe and effective treatment protocols using DNMTi and HDACi.…”
Section: Potential and Challenges Of Epigenetic Therapymentioning
confidence: 99%
“…Therefore, the use of SAHA may increase risk of cancer. However, a very recent study showed that the antioxidant Tempol prevents genotoxicity induced by SAHA and may, potentially, alleviate the long-term risks of the drug [147]. Hence, further detailed studies are required to develop safe and effective treatment protocols using DNMTi and HDACi.…”
Section: Potential and Challenges Of Epigenetic Therapymentioning
confidence: 99%
“…We have recently shown that vorinostat induce oxidative chromosomal damage leading its mutagenic effect in blood lymphocytes [19]. Given the importance of reactive oxygen species, energy metabolism, mitochondrial functions for the antibacterial action of floroquinolones [5][6][7]17], it is probable that these mechanisms has a role in the observed enhancement of ciprofloxacin antibacterial activity by vorinostat.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that the antibacterial activity of ciprofloxacin is altered by major antioxidants, such as, vitamins E and C [17], tempol, pentoxifylline and melatonin [18]. Given that ciprofloxacin acts by inducement of bacterial oxidative damage [5,6], and the known oxidative cell-damaging activity of vorinostat [19], it is likely that vorinostat pretreatmnet enhances ciprofloxacin antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Participants' demographics were obtained using a self-administered questionnaire. The level of dependence on waterpipe smoking was mea-sured using the Lebanon Waterpipe Dependence Scale-11 as previously described (Salameh et al, 2008;Alzoubi et al, 2014a). Investigators were available to answer participants' questions when the questionnaires were filled out and the scaling was conducted.…”
Section: Subjectsmentioning
confidence: 99%
“…Levels of 8-OHdG in the samples were determined using an enzyme-linked immunosorbent assay (ELISA) (8-OH-dG EIA kit; Abcam, Cambridge, UK) according to the manufacturer instructions and as previously described (Alzoubi et al, 2013(Alzoubi et al, , 2014a. Samples were assayed in duplicate.…”
Section: -Ohdg Assaymentioning
confidence: 99%